Investigation of disease outbreaks detected by “syndromic” surveillance systems - Pavlin, Julie A. (Springer-Verlag, 2003)
Syndromic surveillance systems can detect potential disease outbreaks quickly and can provide useful tools to assist in outbreak investigation. The steps used to investigate diseases detected through these newer methods are not that different from traditional investigative measures, but the differences and limitations of the systems must be understood. With syndromic surveillance systems, there is often readily available electronic demographic information that can help define the epidemic and direct disease control measures. The diagnosis needs to be confirmed as quickly as possible, however, as specific diagnostic information will be missing with early detection from nonspecific data. It is also important not to disregard smaller, nonsevere rises in disease incidence as they might be a harbinger of a worsening outbreak. The rapidity of most syndromic surveillance systems also requires an equally rapid response, and planning must be done to prioritize alert categories and the response sequence to best utilize the information available in these new systems.